Perovskite alkali metal samarium borohydrides: Crystal structures and thermal decomposition - Moller, Kasper; Jørgensen, M.; Fogh, A.; Jensen, Torben (R S C Publications, 2017)
© 2017 The Royal Society of Chemistry. A new synthesis method of samarium borohydride, Sm(BH4)2, using tetrahydrofuran borane, THF-BH3, and samarium hydride, SmH2, has been demonstrated and verified. The synthesised Sm(BH4)2was mechanochemically treated with MBH4, M = K, Rb, Cs. Initially, the formation of KSm(BH4)3is observed while subsequent heat treatment is necessary to form MSm(BH4)3, M = Rb, Cs. The new compounds crystallise in orthorhombic unit cells adopting perovskite-type 3D frameworks containing distorted [Sm(BH4)6] octahedra. In situ X-ray diffraction studies reveal two second-order polymorphic transitions of a-CsSm(BH4)3via a tetragonal intermediate, a'-CsSm(BH4)3, into a cubic high-temperature polymorph, ß-CsSm(BH4)3, resembling an ideal perovskite structure. The new compounds, MSm(BH4)3, are thermally stable up to T ~ 280 °C after which they decompose into mainly MBH4, SmH2and possibly SmB6and SmB12H12. Finally, after three cycles of hydrogen release and uptake, the storage capacity was 1.0 wt% for KSm(BH4)3and 0.84 wt% for RbSm(BH4)3and CsSm(BH4)3.